A Theory of Change for Web-Based Therapy and Support Services for Children and Young People: Collaborative Qualitative Exploration - Hanley, Terry; Sefi, Aaron; Grauberg, Janet; Prescott, Julie; Etchebarne, Andre (JMIR Publications, 2021)
BackgroundWeb-based counseling and support has become increasingly commonplace for children and young people (CYP). Currently, there is limited research that focuses on the mechanisms of change within complex telepsychology platforms, a factor that makes designing and implementing outcome measures challenging. ObjectiveThis project aims to articulate a theory of change (ToC) for Kooth, a web-based therapy and support platform for CYP. MethodsA collaborative qualitative research design involving professional staff, academic partners, and young people was used to develop the ToC. The following three major reflective phases were engaged: a scoping workshop involving professional staff and academic partners, a series of explorative projects were completed to inform the development of the ToC, and the draft ToC was reviewed for coherence by key stakeholders (young people, online professionals, and service managers). ResultsA collaboratively developed ToC was presented. This was divided into the conditions that lead to individuals wanting to access web-based therapy and support (eg, individuals wanting support there and then or quickly), the mode of service delivery (eg, skilled and experienced professionals able to build empathetic relationships with CYP), and the observed and reported changes that occur as a consequence of using the service (eg, individuals being better able to manage current and future situations). ConclusionsDeveloping the ToC helps to shed light on how web-based therapy and support services aid the mental health and well-being of CYP. Furthermore, it helps to understand the development of positive virtual ecosystems and can be used to devise evaluative tools for CYP telepsychology providers.